Massage therapy decreases cancer‐related fatigue: Results from a randomized early phase trial. Issue 3 (17th October 2017) - Kinkead, Becky; Schettler, Pamela J.; Larson, Erika R.; Carroll, Dedric; Sharenko, Margaret; Nettles, James; Edwards, Sherry A.; Miller, Andrew H.; Torres, Mylin A.; Dunlop, Boadie W.; Rakofsky, Jeffrey J.; Rapaport, Mark Hyman
Abstract : BACKGROUND: Cancer‐related fatigue (CRF) is a prevalent and debilitating symptom experienced by cancer survivors, yet treatment options for CRF are limited. In this study, we evaluated the efficacy of weekly Swedish massage therapy (SMT) versus an active control condition (light touch [LT]) and waitlist control (WLC) on persistent CRF in breast cancer survivors. METHODS: This early phase, randomized, single‐masked, 6‐week investigation of SMT, LT, and WLC enrolled 66 female stage 0‐III breast cancer survivors (age range, 32‐72 years) who had received surgery plus radiation and/or chemotherapy/chemoprevention with CRF (Brief Fatigue Inventory > 25). The primary outcome was the Multidimensional Fatigue Inventory (MFI), with the National Institutes of Health PROMIS Fatigue scale secondary. RESULTS: Mean baseline MFI scores for 57 evaluable subjects were 62.95 for SMT, 55.00 for LT, and 60.41 for WLC. SMT resulted in a mean (standard deviation) 6‐week reduction in MFI total scores of −16.50 (6.37) (n = 20) versus −8.06 (6.50) for LT (n = 20) and an increase of 5.88 (6.48) points for WLC (n = 17) (treatment‐by‐time P  < .0001). The mean baseline PROMIS Fatigue scores were SMT, 22.25; LT, 22.05; and WLC, 23.24. The mean (standard deviation) reduction in PROMIS Fatigue scores was −5.49 (2.53) points for SMT versus −3.24 (2.57) points for LT and −0.06 (1.88) points for WLC (treatment‐by‐time P  = .0008). Higher credibility, expectancy, and preference for SMT than for LT did not account for these results. CONCLUSION: SMT produced clinically significant relief of CRF. This finding suggests that 6 weeks of a safe, widely accepted manual intervention causes a significant reduction in fatigue, a debilitating sequela for cancer survivors. Cancer 2018;124:546‐54. © 2017 American Cancer Society . Abstract : Cancer‐related fatigue (CRF) is a prevalent and debilitating symptom experienced by cancer survivors, yet treatment options for CRF are limited. Six weeks of a safe, widely accepted manual massage intervention causes a significant reduction in fatigue.